What do people want to know about another person? The answer depends on whether that person is an adult or a child - Matthew I. Billet; Ian Hohm; Rachel M. Dunn; Marlise K. Hofer; Benjamin Sidloski; Mark Schaller (PLoS ONE, 2026)
Research shows that when seeking information about others, people prioritize information about warmth and competence. In those studies, target persons were adults. How might information-seeking priorities differ when that person is a child? In a pilot study ( N = 303), topic modeling of free response data showed that participants expressed relatively less interest in children’s (vs. adults’) dispositions and greater interest in their temperament, health, and needs. In two subsequent experiments ( N ’s = 241 and 717), participants were presented with adult, infant, or non-infant child target persons and rated their interest in obtaining specific information about them. Participants expressed relatively less interest in children’s—especially infants’—warmth and competence, and greater interest in their physical health and curiosity. These results indicate that perceivers’ inferential priorities differ when perceiving persons of different ages. Results are interpreted within a functional perspective on social cognition. Future studies might assess the generalizability of these results across social contexts, cultural contexts, and in elderly targets.